Asparagine endopeptidase deficiency mitigates radiation-induced brain injury by suppressing microglia-mediated neuronal senescence - Ouwen Qiu; Jianyi Zhao; Zhonggang Shi; Huan Li; Siyuan Wang; Keman Liao; Minchao Tang; Jieqiong Xie; Xi Huang; Wenrui Zhang; Li Zhou; Xi Yang; et al. (iScience, 2024)
Summary: Mounting evidence supports the role of neuroinflammation in radiation-induced brain injury (RIBI), a chronic disease characterized by delayed and progressive neurological impairment. Asparagine endopeptidase (AEP), also known as legumain (LGMN), participates in multiple malignancies and neurodegenerative diseases and may potentially be involved in RIBI. Here, we found AEP expression was substantially elevated in the cortex and hippocampus of wild-type (Lgmn+/+) mice following whole-brain irradiation. Lgmn knockout (Lgmn−/−) alleviated neurological impairment caused by whole-brain irradiation by suppressing neuronal senescence. Bulk RNA and metabolomic sequencing revealed AEP’s involvement in the antigen processing and presentation pathway and neuroinflammation. This was further confirmed by co-culturing Lgmn+/+ primary neurons with the conditioned media derived from irradiated Lgmn+/+ or Lgmn−/− primary microglia. Furthermore, esomeprazole inhibited the enzymatic activity of AEP and RIBI. These findings identified AEP as a critical factor of neuroinflammation in RIBI, highlighting the prospect of targeting AEP as a therapeutic approach.